(untitled) (Journal of Universal Science Research, 2026)
This article focuses on how the Task-Based Language Teaching (TBLT) approach can help solve common problems in teaching speaking skills in English language classrooms. Speaking is often considered one of the most difficult skills for students to master because it requires quick thinking, confidence, and the ability to use vocabulary and grammar at the same time. Many learners struggle with fear of making mistakes, limited vocabulary, low motivation, and anxiety when speaking in front of others. The article explains how Task-Based Language Teaching offers a practical solution to these challenges by creating meaningful and realistic communication tasks. Instead of focusing only on grammar rules, students complete tasks such as role-plays, discussions, problem-solving activities, and group projects. These tasks encourage students to use language naturally and interact with their classmates.